Nickel boride and carbon double-layer coated sodium super-ion conductor positive electrode material as well as preparation method and application thereof

By covering the double layer of nickel boride and carbon on the manganese-based NASICON structure core, the conductivity and structural stability of the cathode material of sodium ion battery are solved, and higher cyclic stability and capacity are achieved.

CN120300170AActive Publication Date: 2025-07-11DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510790645.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-13
Publication Date
2025-07-11
Estimated Expiration
2045-06-13

AI Technical Summary

Technical Problem

Existing sodium ion battery positive electrode materials have challenges in energy density and conductivity, especially the structural instability of manganese-based NASICON structural materials during electrochemical cycles.

Method used

The double-layer coating technology of nickel boride and carbon is coated outside the core of manganese-based NASICON structure to form a nickel boride/carbon double-layer coating layer to inhibit the ginger Taylor effect of Mn3+ and improve the conductive properties and structural stability of the material.

Benefits of technology

It significantly improves the cycling stability and capacity of sodium ion batteries, enhances the structural integrity of the material, shortens the diffusion path of sodium ions, improves the rate performance and contact area of the material, and reduces volume expansion during charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120300170A_ABST
    Figure CN120300170A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials, in particular to a nickel boride and carbon double-layer coated sodium super-ion conductor positive electrode material as well as a preparation method and application thereof. The sodium super-ion conductor material comprises a manganese-based NASICON structure inner core and a nickel boride / carbon double-layer coating layer, wherein the manganese-based NASICON structure inner core is coated with the nickel boride / carbon double-layer coating layer; and the chemical formula of the manganese-based NASICON structure inner core is Na3MnTi (PO4) 3. The nickel boride accounts for 1%-10% of the sodium super-ion conductor material in percentage by mass. The sodium-ion battery positive electrode material is obtained by coating the manganese-based NASICON structure inner core with the nickel boride and carbon double coating layers, the ginger-Taylor effect can be effectively inhibited, the conductivity of the material is improved, and the prepared battery is excellent in cycling stability and capacity and has important application value in the field of sodium-ion battery material processing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and particularly to a sodium superionic conductor cathode material coated with nickel boride and carbon bilayer, and its preparation method and application. Background Art

[0002] In the current energy storage field, sodium-ion batteries have become a research hotspot due to their significant advantages in terms of cost, wide resource distribution, and environmental friendliness. Given the abundant reserves of sodium in the earth's crust and its low extraction cost, sodium-ion batteries are regarded as an energy storage technology with broad development prospects, especially in the field of large-scale energy storage system applications. In addition, compared with lithium-ion batteries, sodium-ion batteries exhibit better environmental compatibility in terms of material recycling and reuse.

[0003] Among many sodium-ion battery cathode materials, polyanions have attracted much attention due to their unique structural characteristics and excellent electrochemical properties. Such materials usually have excellent cycle stability. This structural feature of polyanion cathode materials effectively improves the cycle life of sodium-ion batteries and provides an important driving force for the progress of sodium-ion battery technology.

[0004] Although polyanion cathode materials show great potential in sodium-ion battery applications, challenges such as energy density and low conductivity still need to be overcome. Therefore, continuous scientific research and technological innovation are crucial for improving the performance of these materials. Summary of the Invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a sodium superionic conductor cathode material coated with nickel boride and carbon bilayer, and its preparation method and application. By coating with nickel boride and carbon bilayer, the Jahn-Teller effect of manganese is reduced, the conductivity is improved, and the battery prepared has excellent cycle stability and capacity.

[0006] In the first aspect, the present invention provides a sodium superionic conductor material, which includes a manganese-based NASICON structure core and a nickel boride / carbon bilayer coating layer coated outside the manganese-based NASICON structure core; In terms of mass percentage, the nickel boride is 1% - 10% of the sodium superionic conductor material.

[0007] Nickel boride materials have excellent mechanical properties and certain conductivity. In the present invention, the form of coating with nickel boride and carbon bilayer retains the ratio of each element in the main polyanion cathode material on the one hand, and does not change the polyanion structure after coating. On the other hand, it effectively suppresses the Jahn-Teller effect of Mn 3+ to ensure the structural integrity of the material, and the prepared cathode material has excellent cycle stability and capacity.

[0008] Further, in terms of mass percentage, the nickel boride is 1% - 5% of the sodium superionic conductor material.

[0009] Further, the manganese - based NASICON - structured core can be one or more of Na3MnTi(PO4)3, Na4MnV(PO4)3, or Na3MnPO4CO3. Preferably, it is Na3MnTi(PO4)3.

[0010] Further, the mass ratio of the nickel boride to the carbon is (1 - 10):(10 - 20).

[0011] Further, the particle size of the sodium superionic conductor material is 0.5 - 3 μm.

[0012] The sodium superionic conductor material prepared by the present invention has an excellent particle size, which can significantly shorten the diffusion path of sodium ions, improve the rate performance of the material, and enable a higher specific capacity at high rates. In addition, it also has good cycle stability. Compared with large - sized particles, it increases the contact area between the material and the electrolyte, and at the same time reduces the volume expansion of the particles during charge and discharge, thereby improving the structural stability of the material.

[0013] In a second aspect, the present invention provides a pole piece for a sodium - ion battery, which is prepared from the aforementioned sodium superionic conductor material.

[0014] Further, the aforementioned pole piece for a sodium - ion battery, in parts by weight, includes: 5 - 9 parts of the sodium superionic conductor material, 1 - 3 parts of carbon nanotubes, and 0.5 - 2 parts of PVDF.

[0015] In a third aspect, the present invention provides a battery, which is prepared from the aforementioned pole piece for a sodium - ion battery.

[0016] In a fourth aspect, the present invention provides a preparation method of the aforementioned sodium superionic conductor material, including: Mixing a sodium source component, a manganese source component, a titanium source component, a phosphorus source component, and water, and after mixing evenly, obtaining a carbon - coated manganese - based NASICON - structured core through spray drying and calcination; Mixing the carbon - coated manganese - based NASICON - structured core, a nickel source component, and a boron source component, and mixing evenly in an ethanol solvent environment for 2 - 6 hours, followed by centrifugation and drying.

[0017] Further, the sodium source component includes at least one of sodium carbonate, sodium hydroxide, sodium chloride, sodium acetate, sodium citrate, or sodium bicarbonate; The manganese source component includes at least one of manganese nitrate, manganese chloride, manganese acetate, or manganese acetylacetonate; The titanium source component includes at least one of tetrabutyl titanate, tetraethyl titanate, isopropyl titanate, or diammonium titanium dihydroxide bis(2-hydroxypropionate); The nickel source component includes at least one of nickel chloride, nickel nitrate, nickel sulfate, or nickel acetate; The boron source component is sodium borohydride or boric acid; The mass ratio of the carbon-coated manganese-based NASICON structure core, nickel source component, and boron source component is 1:(0.03 - 0.1):(0.001 - 0.01).

[0018] The inlet temperature of the spray drying is 100 - 200 °C, the air intake is 60 - 90%, and the feeding rate is 1 - 5 mL / min; The temperature of the calcination is 500 - 800 °C, and the time is 3 - 10 h.

[0019] Further, the temperature of the calcination is 600 - 800 °C, and the time is 4 - 7 h.

[0020] Further, the temperature of the calcination is independently selected from any value of 600 °C, 650 °C, 700 °C, 7500 °C, 800 °C or the range value between any two of the above.

[0021] Further, the time of the calcination is independently selected from any value of 4 h, 5 h, 6 h, 7 h or the range value between any two of the above.

[0022] Preferably, after calcination at 650 °C for 4 hours, the performance of the Na3MnTi(PO4)3 cathode material coated reaches the optimum.

[0023] In a fifth aspect, the present invention provides the application of the foregoing sodium superionic conductor material in the preparation of a sodium ion battery.

[0024] Further, the foregoing sodium superionic conductor material is ground for more than 30 minutes and ground for more than 3 hours in an NMP solvent environment according to the ratio of the foregoing electrode sheet for a sodium ion battery, and then coated on an aluminum foil and vacuum dried to obtain an electrode sheet for a sodium ion battery.

[0025] Furthermore, the obtained electrode sheet for a sodium ion battery is assembled as a positive electrode sheet in the order of a positive electrode case, a positive electrode sheet, a separator, a sodium sheet, a gasket, a spring piece, and a negative electrode case, and an electrolyte is dropped to obtain a sodium ion battery.

[0026] The electrolyte includes: an EC:PC solution of 0.5 - 2 M NaClO4 and 3 - 10% fluoroethylene carbonate (FEC).

[0027] The present invention has the following beneficial effects: The present invention coats a double coating layer of nickel boride and carbon on the core of a manganese-based NASICON structure. Compared with existing manganese-based NASICON materials, it exhibits better capacity and cycling stability during the electrochemical cycling process, promoting the application of NASICON materials in sodium-ion batteries.

[0028] The preparation process of the sodium superionic conductor material provided by the present invention is simple and environmentally friendly, and can be applied to the production process of large-scale products. Brief Description of the Drawings

[0029] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the drawings in the following description are some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.

[0030] Figure 1 XRD patterns of various samples (NMTP, NMTP / C, and NMTP / C@Ni x B) in Example 1 of the present application, where NMTP is Na3MnTi(PO4)3, NMTP / C is Na3MnTi(PO4)3 / C, and NMTP / C@Ni x B is Na3MnTi(PO4)3 / C@Ni x B.

[0031] Figure 2 SEM images of various samples (NMTP, NMTP / C, and NMTP / C@Ni x B) in Example 1 of the present application.

[0032] Figure 3 TEM images of various samples (NMTP, NMTP / C, and NMTP / C@Ni x B) in Example 1 of the present application.

[0033] Figure 4 EDS images of NMTP / C@Ni x B in Example 1 of the present application.

[0034] Figure 5 Discharge curves of various samples (NMTP, NMTP / C, and NMTP / C@Ni x B) at 0.2C in Example 1 of the present application.

[0035] Figure 6 Cycling stability tests of various samples (MTP, NMTP / C, and NMTP / C@Ni x B) at 1C in Example 1 of the present application.

[0036] Figure 7 For each sample (MTP, NMTP / C, and NMTP / C@Ni x B) in Experimental Example 1 of this application, the FIB-SEM images after the stability test are shown below. Detailed implementation manners

[0037] To make the objectives, technical solutions, and advantages of the present invention clearer, the technical solutions in the present invention will be clearly and completely described below with reference to the accompanying drawings in the present invention. Apparently, the described embodiments are some, but not all, of the embodiments of the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative efforts based on the embodiments in the present invention belong to the scope of protection of the present invention.

[0038] Unless otherwise specified, the experimental methods involved in the following examples are all conventional methods in the art. For example, reference can be made to the experimental manuals in the art or the conditions recommended in the manufacturer's instructions.

[0039] Unless otherwise specified, the experimental materials and reagents involved in the following examples can all be obtained commercially.

[0040] In the following examples, a Neware battery test system was used for constant current charge and discharge tests (cut-off voltage 2.0 - 4.2V, currents 0.2C and 1C, where 1C = 135 mAh / g); a JEF-2100 transmission electron microscope was used to observe the sample morphology; and a Bruker D8 from Germany was used to test the XRD of the samples.

[0041] In the following examples: NMTP is Na3MnTi(PO4)3, NMTP / C is Na3MnTi(PO4)3 / C, and NMTP / C@Ni x B is Na3MnTi(PO4)3 / C@Ni x B.

[0042] Example 1

[0043] The present invention provides a method for preparing Na3MnTi(PO4)3 / C@Ni x B and applying the same to battery preparation, including the following process: 1. Prepare Na3MnTi(PO4)3 / C@Ni x B (1) Add 10 mmol of citric acid monohydrate to 100 mL of deionized water and dissolve it completely at room temperature. Subsequently, add 5 mmol of manganese acetate tetrahydrate and sodium dihydrogen phosphate dihydrate, and then add 5 mmol of diammonium titanium(IV) bis(2-hydroxypropionate) dihydroxide and stir evenly to carry out spray drying. Spray drying parameters: inlet temperature 200 °C, suction rate 90%, feed rate 3 mL / min. Then collect the samples.

[0044] (2) Collect the obtained powder and calcine it in an argon furnace at 650 °C for 4 h. Immediately take it out after the furnace temperature drops to 100 °C and store it in a glove box to obtain Na3MnTi(PO4)3 / C for later use.

[0045] (3) Disperse 2.5 g of the Na3MnTi(PO4)3 / C cathode material in ethanol, add 112 mg of nickel acetate tetrahydrate and 5.9 mg of sodium borohydride, stir for 4 h, and then centrifuge and dry to obtain the target sample Na3MnTi(PO4)3 / C@Ni x B.

[0046] The present invention further detects Na3MnTi(PO4)3 / C@Ni x B. Its particle size is 2 μm, and the content of Ni x B is 3 wt%, and the content of C is 13 wt%.

[0047] The present invention further performs X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and energy-dispersive X-ray spectroscopy (EDS) tests on the obtained target samples, and obtains the results as Figures 1-4 shown.

[0048] As Figure 1 shown, it can be seen from Figure 1 that the two samples prepared by this method have the typical structure of polyanionic Na3MnTi(PO4)3, and the coating does not affect the crystal structure of the material.

[0049] As Figure 2 , Figure 3 shown, it can be seen from Figure 2 , Figure 3 that the two samples prepared by this method have similar structural morphologies. At the same preparation temperature and time, the coating does not affect the morphology of the material; but there is a layer of other substances shown on the outermost layer after coating.

[0050] As Figure 4 shown, it can be seen from Figure 4 that the elements are evenly distributed after coating, and the elements of the coating material are mainly distributed on the outermost layer, indicating the successful coating of the material.

[0051] 2. Preparation and assembly of the electrode for sodium-ion battery using Na3MnTi(PO4)3 / C (1) Weigh the polyanion-type cathode material prepared in Step 1, i.e., the active material, and other substances according to the mass ratio of 350 mg active material: 100 mg carbon nanotubes: 50 mg PVDF = 7:2:1. Then grind them in the glove box. After 30 minutes, add 700 μL of NMP solvent and continue grinding for 3 hours. Then use a 300 μm scraper to evenly coat the slurry on the aluminum foil.

[0052] (2) Transfer the aluminum foil coated with the slurry to a vacuum drying oven and dry it at 120 °C for 12 hours to obtain the coated polyanion-type Na3MnTi(PO4)3 cathode material.

[0053] 3. Assemble the button battery for testing using the coated polyanion-type Na3MnTi(PO4)3 cathode material obtained in Step 2. The specific steps are as follows: Assemble in the order of the positive electrode case, positive electrode sheet, separator, sodium sheet, gasket, spring piece, and negative electrode case, and drop 100 μL of electrolyte (EC:PC solution of 1.0 M NaClO4 + 5% FEC). After standing for 12 hours, cyclic charge-discharge tests (voltage window 2.0 - 4.0 V) can be carried out.

[0054] As Figure 5 shown, at a current density of 0.2C, Na3MnTi(PO4)3 / C@Ni x B (3 wt%) has the best electrochemical performance.

[0055] As Figure 6 shown, after 200 cycles of NMTP at 1C, its capacity drops sharply. After 1000 cycles of NMTP / C, its capacity retention rate is only 62.5%. While for Na3MnTi(PO4)3 / C@Ni x B (3 wt%), after 2000 cycles, its capacity retention rate reaches 73.5%. It shows that the cyclic stability of the coated material is effectively enhanced, and Ni x B plays a certain inhibitory role on the 3+ Jahn-Teller effect.

[0056] Experimental Example 1 Further, the battery prepared in Example 1 of the present invention is subjected to constant current charge-discharge tests on the Neware system, and then the battery is disassembled for FIB-SEM tests. The specific steps are as follows: Set the charge and discharge procedure as follows: Stand still for 30 s, charge at 0.1C, stand still for 30 s, discharge at 0.1C. When the number of cycles is less than 500, return to the first step to complete the cyclic charge and discharge test of the battery. After 500 cycles, disassemble the battery, obtain the positive electrode and scrape off the powder. After drying, the FiB-SEM test can be carried out.

[0057] The results are as Figure 7 shown. After cycling, obvious cracks appear on the surface of NMTP. It can be clearly observed from its cross-sectional view that there are obvious cracks. Although NMTP / C also has crack distribution, compared with NMTP, the number of cracks is significantly reduced. In contrast to the two materials, NMTP / C@Ni x B does not generate obvious cracks after cycling, indicating that the material has good structural stability, indicating that Ni x B has a certain inhibitory effect on the 3+ Jahn-Teller effect.

[0058] Experimental Example 2 The present invention further prepares Na3MnTi(PO4)3 / Ni x B, and the method is as follows: Dissolve 5 mmol of manganese acetate tetrahydrate and sodium dihydrogen phosphate dihydrate in 100 mL of deionized water, and then add 5 mmol of diammonium dihydroxide bis(2-hydroxypropionate) titanate and stir evenly for spray drying. Spray drying setting parameters: inlet temperature 200 °C, air intake 90%, feed rate 3 mL / min. Then collect the sample. (2) Collect the obtained powder and heat it in an air furnace at 650 °C for 4 h. Immediately take it out and store it in a glove box after the furnace temperature drops to 100 °C to obtain Na3MnTi(PO4)3. (3) Disperse 2.5 g of Na3MnTi(PO4)3 positive electrode material in ethanol, add 112 mg of nickel acetate tetrahydrate and 5.9 mg of sodium borohydride, stir for 4 h and then centrifuge and dry to obtain the target sample Na3MnTi(PO4)3@Ni x B.

[0059] The prepared Na3MnTi(PO4)3 / Ni x B material (particle size: 2 μm, Ni x B content: 3%) is prepared into a battery by the same method as in Example 1, and a constant current charge and discharge test and the same cyclic stability detection experiment as in Experimental Example 1 are carried out. The results show that although the material stability is improved, the material capacity is reduced by more than half.

[0060] This shows that the capacity of the Na3MnTi(PO4)3 / Ni x B material obtained by simply coating Ni x B decreases, and the improvement effect of cyclic stability is limited. The double-layer coating of C and Ni in the present invention xB combines significantly higher capacity and cycling stability.

[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements for some of the technical features; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the various embodiments of the present invention.

Claims

1. A sodium superionic conductor material, characterized in that, The sodium superionic conductor material includes a manganese-based NASICON structure core and a nickel boride / carbon double coating layer coated on the outside of the manganese-based NASICON structure core; By mass percentage, the nickel boride is 1% - 10% of the sodium superionic conductor material; The chemical formula of the manganese-based NASICON structure core is Na3MnTi(PO4)3.

2. The sodium superionic conductor material according to claim 1, wherein, The mass ratio of the nickel boride to the carbon is (1 - 10):(10 - 20).

3. The sodium superionic conductor material according to claim 1 or 2, characterized in that, The particle size of the sodium superionic conductor material is 0.5 - 3 μm.

4. A pole piece for a sodium-ion battery, characterized in that, Prepared from the sodium superionic conductor material according to any one of claims 1 - 3.

5. The electrode sheet for a sodium ion battery according to claim 4, characterized in that, By weight, it includes: 5 - 9 parts of the sodium superionic conductor material, 1 - 3 parts of carbon nanotubes, and 0.5 - 2 parts of PVDF.

6. A battery, characterized in that, Prepared from the electrode sheet for sodium ion battery according to claim 4 or 5.

7. The preparation method of the sodium superionic conductor material according to any one of claims 1-3, characterized in that, Includes: Mix the sodium source component, manganese source component, titanium source component, phosphorus source component and water, and after mixing evenly, obtain the carbon-coated manganese-based NASICON structure core through spray drying and calcination; Mix the carbon-coated manganese-based NASICON structure core, nickel source component and boron source component, and mix evenly for 2 - 6 hours in an ethanol solvent environment, and then centrifuge and dry.

8. The preparation method according to claim 7, wherein The sodium source component includes at least one of sodium carbonate, sodium hydroxide, sodium chloride, sodium acetate, sodium citrate or sodium bicarbonate; and / or, The manganese source component includes at least one of manganese nitrate, manganese chloride, manganese acetate or manganese acetylacetonate; and / or, The titanium source component includes at least one of tetrabutyl titanate, tetraethyl titanate, isopropyl titanate or diammonium bis(2-hydroxypropionate) dihydroxytitanate; and / or, The nickel source component includes at least one of nickel chloride, nickel nitrate, nickel sulfate or nickel acetate; and / or, The boron source component is sodium borohydride or boric acid; and / or, The inlet temperature of the spray drying is 100 - 200 °C, the air intake is 60 - 90%, and the feeding rate is 1 - 5 mL / min; and / or, The temperature of the calcination is 500 - 800 °C, and the time is 3 - 10 h.

9. Application of the sodium superionic conductor material according to any one of claims 1 - 3 in the preparation of a sodium ion battery.

Citation Information

Patent Citations

  • Layered copper oxide-contained material and preparation method and application thereof

    CN104795551A

  • Sodium-ion battery negative electrode material and preparation method thereof

    CN107093712A

  • Carbon-coated vanadium titanium manganese sodium phosphate microspheres as well as preparation method and application thereof

    CN113764662A

  • Manganese-based NASICON type sodium ion positive electrode material and preparation method and application thereof

    CN114373922A

  • Apparatus for managing article in vehicle and method thereof

    KR1020210124791A